Effects of Polystyrene Microplastic Exposure on Liver Cell Damage, Oxidative Stress, and Gene Expression in Juvenile Crucian Carp (Carassius auratus) - Xiangtong Li; Yuequn Huang; Wenrong Li; Chaoyang Deng; Weiyuan Cao; Yi Yao (Toxics)
A considerable quantity of microplastic debris exists in the environment and the toxicity of these materials has a notable impact on aquatic ecosystems. In this paper, 50–500 µm polystyrene microplastics (exposure concentrations were 200 µg/L, 800 µg/L, and 3200 µg/L concentrations) were selected to study the effects of polystyrene microplastics (PS-MPs) on cell morphology, detoxification enzyme activity, and mRNA expression in the liver tissues of crucian carp juveniles. The results demonstrated that: (1) Different concentrations of PS-MPs cause varying degrees of pathological and oxidative damage to liver tissue cells of crucian carp. The higher the concentration of microplastics, the lower the antioxidant enzyme (CAT, GST, SOD) activity and the greater the tissue cell damage. These results demonstrate a typical dose–effect relationship. (2) Principal component analysis and Spearman’s correlation analysis demonstrated that four components, namely glutathione S-transferase (GST) and its related genes (GSTpi, GSTα), along with catalase (CAT), contributed the most to the observed outcome. These four components demonstrated a relatively high level of responsiveness to PS-MP exposure and can be employed as ecotoxicological indicators of microplastics. (3) This experiment evaluated five genes in three treatments, which found that PS-MPs had different effects on gene expression in the liver and the tested genes were involved in different response pathways associated with virulence. In this study, the toxicity of PS-MPs to crucian carp was determined at the cellular, protein, and mRNA expression levels, and combined with principal component analysis and correlation analysis to identify response sensitivity indicators that provide a scientific basis for ecological risk assessment and the safe use of microplastics.